A study of genetic population of Alosa braschnicowi (Borodin, 1904) in Sari and Mahmodabad coasts in the Caspian Sea, using Microsatellite loci - Omid Jafari (International Journal of Aquatic Biology, 2014)
In this study, five Microsatellite loci were used to evaluate genetic diversity of A. braschnicowi between two populations of the Caspian Sea. Sixty samples were collected from the coasts of Mahmodabad and Sari (30 specimens for each population). Five Microsatellite loci were highly polymorphic among all samples. The number of alleles per locus observed ranged from 17 to 32 and averaged 14.1 alleles across two populations. The average observed heterozygosis in Mahmodabad and Sari were 57.1% to 60.1% and average observed heterozygosis between two populations was 58.9%. Among 10 population-locus (5 loci × 2 populations) only two tests were in the Hardy-Weinberg equilibrium, so highly deviation from the Hardy-Weinberg equilibrium was found. The average values of Fis and Nm were 0.33 and 14.19, respectively. Also AMOVA on base Fst index showed low genetic difference between two populations (2%), while the genetic diversity within population was 98%. Due to allelic diversity and estimates of heterozygosity, these markers can be useful in Alosa genus for population level analysis in the Caspian Sea.